Perilaku Teganga-Regangan Beton Ringan Densitas Rendah yang dikonfin oleh FRP - Butje Alfonsius Louk Fanggi; Hazen Masrafat; Joko Suparmanto; Abdul Syukur Hadi Suwito; Indradhi Lasmana (Universitas Islam 45, 2026)
This study investigates the axial compressive behaviour of very-low-density lightweight concrete confined with fibre-reinforced polymer (FRP) jackets to improve understanding of its structural performance. The research aims to evaluate how confinement level, concrete strength, density, and fibre type influence confined strength and ductility in square sections. An experimental program was conducted using 150 mm × 150 mm × 300 mm lightweight concrete specimens with a target density of approximately 1550 kg/m³, wrapped with carbon FRP (CFRP) and glass FRP (GFRP) in two-an- three-layer configurations. Axial compression tests were used to establish stress–strain relationships and to determine key parameters, including confined strength ratio and ultimate strain ratio. The results show that FRP confinement produces substantial increases in both compressive strength and strain capacity, with fʹcu/fʹc values up to about 3.29 and εcu/εco ratios exceeding 20, confirming the high confinement efficiency attainable in very-low-density mixes. Higher strength concrete achieved greater ultimate stress but lower ultimate strain, whereas lower density concrete developed larger ultimate strains under effective jacketing. Comparisons between CFRP and GFRP revealed that, in some cases, GFRP confinement provided comparable or superior enhancement of strength and deformability, emphasising the role of material compatibility and installation quality. Overall, the findings extend the experimental database for FRP-confined lightweight concrete at densities near 1550 kg/m³ and highlight the need for refined predictive models and design provisions tailored to this density range.